A New Fluorescent Chemodosimeter for Hg2+ with High Selectivity and Sensitivity in Water. Issue 5 (24th October 2016) - Yang, Dengchen; Li, Meng; Chen, Chuanfeng
Abstract : A new fluorescent chemodosimeter based on tetrahydro[5]helicene imide was synthesized, and it showed high selectivity and sensitivity toward Hg 2+ ions over other different tested metal ions in water. The response time was within 0.5 min, and the detection limit of the chemodosimeter for Hg 2+ was estimated to be 2.0 × 10 −8 molL −1 . The Hg 2+ promoted deprotection of dithioacetal groups of1, which induced water‐soluble fluorescent chemodosimeter1 to form a water‐insoluble aldehyde precursor. Abstract : A new fluorescent chemodosimeter1 based on tetrahydro[5]helicene imide was synthesized, and it showed high selectivity and sensitivity toward Hg 2+ in water. The response time was within 0.5 min, and the detection limit of1 for Hg 2+ was 2.0 × 10 −8 molL −1 . Moreover, the response mechanism that Hg 2+ promoted deprotection of dithioacetal groups of1 to form its water‐insoluble aldehyde precursor was also proposed.